2020
DOI: 10.1159/000509254
|View full text |Cite
|
Sign up to set email alerts
|

An Abnormal Precone Endocervical Curettage Result Is an Independent Risk Factor for Positive Margins in Conization Specimens

Abstract: This study aimed to identify risk factors associated with the presence of positive surgical margins in cervical conization specimens. Methods: This study is a retrospective analysis of data from women who had undergone conization for cervical intraepithelial neoplasia (CIN) from 2012 to 2018 at Fujian Maternity and Child Health Hospital. Factors extracted from the database included age, gravidity, parity, menopausal status, precone Thinprep cytology test, human papillomavirus (HPV) test, precone biopsy, precon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The proportion of residual lesions after LEEP was 43.48%. Therefore, for these patients, we should adopt more active treatment ( 21 ), and the conization depth should be properly increased to prevent positive postoperative margins. ECC was performed immediately after conical resection to remind the possibility of residual lesions in the cervical canal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of residual lesions after LEEP was 43.48%. Therefore, for these patients, we should adopt more active treatment ( 21 ), and the conization depth should be properly increased to prevent positive postoperative margins. ECC was performed immediately after conical resection to remind the possibility of residual lesions in the cervical canal.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that when the ECC result was higher than the pathological result of targeted biopsy, the positive rate of LEEP resection margin or ECC after surgery was 32.08%, which may be related to the type of lesion in the cervical canal. Therefore, during the operation, doctors should appropriately increase the depth of conization and perform ECC immediately after cervical coning to avoid a missed diagnosis in the residual cervical canal ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, positive ectocervical margin also significantly impacted the risk of developing persistent/recurrent disease. Moreover, we have to take into consideration that the severity of the dysplasia might correlate with the size of the cervical lesions [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of positive LEEP residue was as high as 12-26% [9,10,13,14]. Some studies have confirmed that the risk factors associated with CIN 2/3 residue include residual margin, lesion size, lesion severity and location, depth and method of excision, patient age and menopausal status, and the presence of HR-HPV after excision [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 97%